Endothelial markers are associated with thrombolysis resistance in acute stroke patients. (4th February 2014) - Faille, D.; Labreuche, J.; Meseguer, E.; Huisse, M.‐G.; Ajzenberg, N.; Mazighi, M.
<x xml:space="preserve">Abstract</x> Background and purpose The endothelium is crucial in maintaining the haemostatic balance between pro‐ and anti‐thrombotic factors. In this pilot study, the association of endothelial biomarkers with arterial recanalization and clinical outcome in the setting of acute ischaemic stroke (AIS) was evaluated amongst patients treated with recombinant tissue plasminogen activator (rt‐PA). Methods Sixty‐four AIS patients treated with rt‐PA were prospectively recruited. Blood was collected before thrombolysis and analysed for von Willebrand factor (vWF), soluble thrombomodulin (sTM) and soluble endothelial protein C receptor (sEPCR). Complete recanalization was defined by a Thrombolysis in Myocardial Infarction Score of 3. Favourable clinical outcome was defined by a modified Rankin Score of 0–2 at 90 days. Results Amongst the 64 patients, 31 had no documented occlusion, 19 had persistent occlusion and 14 had complete recanalization. After adjustment for confounding factors, these patients presented lower sTM and sEPCR levels than patients with persistent occlusion (median sTM, 21 vs. 48 ng/ml, P = 0.008; median sEPCR, 78 vs. 114 ng/ml, P = 0.018), but similar levels compared with patients without occlusion. vWF levels did not differ between groups. None of these biomarkers was significantly associated with favourable outcome. Conclusions Recanalization after thrombolytic therapy is associated with low sTM and sEPCR levels but not with vWF levels. If corroborated in further larger studies, these findings could be helpful in the identification of patients resistant to rt‐PA thrombolysis who could benefit from a modified recanalization therapy.